Peatlands and creatures great and small: part II – invertebrates - Locky, David (My University, 2004)
This article is the last of a two-part series on peatland creatures. Here, I focus on peatlands and invertebrates and some microfauna, and then outline wetlands from the perspective of conservation and creatures of all sizes. A table with peatland creatures, great and small, is included.
Keywords: peatlands; wetlands; Canada